2019
DOI: 10.7554/elife.46012
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 interlinks integrin and hippo pathway to autoregulate tip cell activity

Abstract: CCN1 (CYR61) stimulates active angiogenesis in various tumours, although the mechanism is largely unknown. Here, we report that CCN1 is a key regulator of endothelial tip cell activity in angiogenesis. Microvessel networks and directional vascular cell migration patterns were deformed in ccn1-knockdown zebrafish embryos. CCN1 activated VEGFR2 and downstream MAPK/PI3K signalling pathways, YAP/TAZ, as well as Rho effector mDia1 to enhance tip cell activity and CCN1 itself. VEGFR2 interacted with integrin αvβ3 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 85 publications
3
33
0
Order By: Relevance
“…Tip cells are located at the ends of angiogenic sprouts and their filopodial protrusions directed vessel growth toward angiogenic attractants 57 59 . Recent data showed that Cyr61 , a known YAP/TAZ target gene, stimulates tip cell proliferation and activity 60 . Therefore, loss of endothelial Wwc2 expression might activate YAP/TAZ-dependent Cyr61 expression that in turn leads to enhanced tip cell activity and disturbed vessel sprouting.…”
Section: Discussionmentioning
confidence: 99%
“…Tip cells are located at the ends of angiogenic sprouts and their filopodial protrusions directed vessel growth toward angiogenic attractants 57 59 . Recent data showed that Cyr61 , a known YAP/TAZ target gene, stimulates tip cell proliferation and activity 60 . Therefore, loss of endothelial Wwc2 expression might activate YAP/TAZ-dependent Cyr61 expression that in turn leads to enhanced tip cell activity and disturbed vessel sprouting.…”
Section: Discussionmentioning
confidence: 99%
“…One possible alternative mechanism is through CCN protein upregulation, as this has been shown to induce ER-stress and UPR-activation in both stellate cells and hepatocytes by in vitro and in vivo approaches. CCN proteins are ECM-associated secreted proteins which play a role in a with a wide array of important functions, such as wound healing and tumorigenesis ( Park et al, 2019 ). Adenoviral CCN gene transfer and overexpression of CCN proteins have been shown to induce ER-stress-mediated stellate cell senescence and apoptosis in later stages of fibrosis, consequently contributing to fibrosis resolution ( Borkham-Kamphorst et al, 2016 ; Borkham-Kamphorst et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The foreign-body reaction starts with layer of proteins that come from blood and interstitium immediately forming on the surface of biomaterial after implantation, which activates inflammatory reaction of related cells as a result (Wilson et al, 2005;Singhatanadgit et al, 2019). Researches on enhancing the biocompatibility of implant material have been a hot topic in dentistry, for instance, surface modification (Hamlet and Ivanovski, 2011;Hamlet et al, 2012;Palmquist et al, 2013;Fukuda et al, 2019). as well as changing the design and composition of implants (Cooper et al, 2016;Wang Y. et al, 2019) are generally proposed as available strategies.…”
Section: Osteogenesis Angiogenesis and Osteoimmunology And Their Effmentioning
confidence: 99%
“…Mechanistically, YAP/TAZ promotes migration of tip cells by activating CDC42 and facilitates the formation and junction of filopodia, an essential dynamic structure of tip cell that dominates its sprouting function, by promoting the remodeling of actin cytoskeleton ( Kim et al, 2017 ; Sakabe et al, 2017 ). Likewise, the identity of tip cells are induced by CCN1, through interaction with integrin αvβ3/VEGFR and activation of downstream Hippo pathway thus promoting nucleus translocation of YAP/TAZ, which coordinates CCN1 in turn as a positive feedback ( Park et al, 2019 ). While overactivating YAP/TAZ leads to pathologic sprouting pattern ( Astone et al, 2018 ).…”
Section: Role Of Hippo-yap Signaling In Osteogenesis Angiogenesis Anmentioning
confidence: 99%